Right to healt among public school adolescents: A narrative review (Research, Society and Development, 2023)
Health education is presented as a social right that must be understood by adolescents, with the school as a facilitating agent. The objective was to analyze the right to health among adolescents from public schools through a narrative review. To this end, a narrative review was used, regarding the interventions implemented in health in the school environment and reflected in the lives of these students, in the period of June and July 2023. , the results obtained are related to the promotion of health within this age group, such as physical health, with the need to adopt measures for a good quality of life and subsequently the psychological approach of these students as a fundamental factor in the development, and it is still possible to build a characteristic social profile in this phase. Thus, it is concluded that the right to health of public school adolescents is an important issue that requires attention from all those involved. Through a comprehensive analysis, it was possible to verify that access to health services is a fundamental need for this group, given its importance for their physical, mental and social development.